La mise en lumière des indépendants. Le mythe de l’artiste isolé chez les écrivains symbolistes français - Lucbert, Françoise (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1999)
Inspired by the thinking of art sociologists like Nathalie Heinich, Pierre Bourdieu and Dario Gamboni, this article examines how a particular group of writers on the rise, the symbolist generation active in the late nineteenth century, engaged in promoting a certain artistic ideal that would in return enhance and legitimize their own aesthetic agenda and position. The young novelists and poets writing art criticism in the small literary magazines that proliferated in symbolist circles became the champions of the new independent painters exhibiting outside traditional art institutions. Going against the grain of positivist thinking, that tied the art producer to his own historic, geographic and social circumstances, they resuscitated the romantic figure of the misunderstood solitary genius, at once a saint and a prophet, towering above the crowd and waiting to be discovered. This was, of course, the very image they wanted to project of themselves. That is why they remained faithful to this archetype, even in the face of professional success, their protégés’ and their own.